2004
DOI: 10.2139/ssrn.530685
|View full text |Cite
|
Sign up to set email alerts
|

The Improving Relative Status of Black Men

Abstract: Using data from the Current Population Survey, we examine recent trends in the relative economic status of black men. Our findings point to gains in the relative wages of black men (compared to whites) during the 1990s, especially among younger workers. In 1989, the average black male worker (experienced or not) earned about 69 percent as much per week as the average white male worker. In 2001, the average younger black worker was earning about 86as much as an equally experienced white male; black males at all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The ratio of these two rates, 2.3, is consistent with the observation that unemployment among blacks typically doubles that of whites. 1 The stability of this unemployment ratio has been noted (Welch, 1990 andSmith, Vanski, andHolt 1974) as an anomaly that stands in contrast to measured increases in relative black wages observed in the past three decades (Welch 2003, Couch and Daly 2002, 2005. 2 Many have conjectured that the relative constancy of the difference in black and white unemployment is due to minorities being the last hired and first fired over the business cycle (Harrington 1962, Freeman 1973, Barrett and Morgenstern 1974, Browne 1997, and Bradbury 2000.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of these two rates, 2.3, is consistent with the observation that unemployment among blacks typically doubles that of whites. 1 The stability of this unemployment ratio has been noted (Welch, 1990 andSmith, Vanski, andHolt 1974) as an anomaly that stands in contrast to measured increases in relative black wages observed in the past three decades (Welch 2003, Couch and Daly 2002, 2005. 2 Many have conjectured that the relative constancy of the difference in black and white unemployment is due to minorities being the last hired and first fired over the business cycle (Harrington 1962, Freeman 1973, Barrett and Morgenstern 1974, Browne 1997, and Bradbury 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies in Israel have focussed on FSU immigrants, while ignoring Ethiopian immigrants who are black-skinned and thus differ from both FSU immigrants and native Jews in that respect. Researchers in the USA, including Couch and Daly (2004), Smith and Welch (1977), Blau and Beller (1992) and Card and Krueger (1992), have found that the earnings of native whites are higher than those of native blacks. Chiswick (1978) found that immigrants in the USA earn less than natives in the period following their arrival [5].…”
mentioning
confidence: 99%
“…Work by Couch and Daly (, ) casts doubt on the importance of exits of lower qualified blacks in inflating the progress of relative black to white pay by examining trends in black to white pay over the boom period of the 1990s. If marginally qualified black workers are drawn into the labor market during a period of low unemployment, relative wage progress should fall.…”
Section: The Effects Of Title VII On Labor Market Outcomesmentioning
confidence: 99%